2013
DOI: 10.4250/jcu.2013.21.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Role of Imaging in the Detection of Reversible Cardiomyopathy

Abstract: Heart failure is a major clinical problem in developed countries with about half of heart failure patients exhibiting decreased left ventricular systolic function. The correct identification and prompt treatment of some specific etiologies can reverse heart failure, and recognition of myocardial recovery may avoid long-term therapy. However, the echocardiographic patterns of patients with a variety of etiologies of heart failure are similar, so the selective use of other imaging techniques is necessary for ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 101 publications
0
8
0
2
Order By: Relevance
“…It allows to differentiate FD from sarcomeric HCM, which usually results in LGE at the right ventricular (RV) junction points, and amyloidosis, which usually results in a global subendocardial pattern of LGE [51]. However, this LGE pattern is not exclusive of FD and may also be found in myocarditis, Chagas disease, and sarcoidosis [52]. A binary appearance of the LV endocardial border, known as the "binary sign," was correlated with a characteristic pattern of glycosphingolipid compartmentalization on histological examination and once thought to represent a hallmark feature of Fabry cardiomyopathy [42].…”
Section: Left Ventricular Storage Inflammation and Fibrosismentioning
confidence: 99%
“…It allows to differentiate FD from sarcomeric HCM, which usually results in LGE at the right ventricular (RV) junction points, and amyloidosis, which usually results in a global subendocardial pattern of LGE [51]. However, this LGE pattern is not exclusive of FD and may also be found in myocarditis, Chagas disease, and sarcoidosis [52]. A binary appearance of the LV endocardial border, known as the "binary sign," was correlated with a characteristic pattern of glycosphingolipid compartmentalization on histological examination and once thought to represent a hallmark feature of Fabry cardiomyopathy [42].…”
Section: Left Ventricular Storage Inflammation and Fibrosismentioning
confidence: 99%
“…To improve cardiac function in CSS patients with DCMP, the early identification of cardiac involvement by multi-modality imaging and appropriate medical therapy would be of importance. 14) Considering the pathophysiologic mechanism of DCMP in patients with CSS, immunosuppressive therapy to control disease activity of CSS should be included, in addition to conventional medical therapy for heart failure including blocking agents for renin-angiotensin-aldosterone system and beta-blockade. The previous study have shown that high dose steroid and chemotherapy with cyclophosphamide are the most effective treatment of cardiac involvement of CSS, even though cyclophosphamide has a potential of cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…T1 mapping will show increased values; this is especially useful in patients with unremarkable LGE. Patients with edema have increased native T2 values compared with those in normal subjects [33,34] (Figs. 4 and 5).…”
Section: A B C D Ementioning
confidence: 99%